2022
DOI: 10.3390/ijms23052901
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Myotonic Dystrophy Type 1 with Metformin

Abstract: Myotonic dystrophy type 1 (DM1) is a multisystemic disorder of genetic origin. Progressive muscular weakness, atrophy and myotonia are its most prominent neuromuscular features, while additional clinical manifestations in multiple organs are also common. Overall, DM1 features resemble accelerated aging. There is currently no cure or specific treatment for myotonic dystrophy patients. However, in recent years a great effort has been made to identify potential new therapeutic strategies for DM1 patients. Metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 130 publications
(188 reference statements)
2
13
0
Order By: Relevance
“…This target seems to be involved in both DM1 and DM2 pathogeneses because both DM1 and DM2 are characterized by insulin resistance and predisposition to type 2 diabetes (T2D) [ 3 , 4 , 5 , 6 ]. It was shown that an anti-diabetic drug, metformin, corrects abnormal IR splicing in DM1 mesodermal precursor cells (MPCs) and in DM1 myoblasts ([ 78 ] and reviewed in [ 79 ]). Interestingly, in addition to IR, metformin also improves splicing of other genes, including TNNT2 and Clcn1 [ 78 ].…”
Section: Therapeutic Targets In Dm1 and Dm2mentioning
confidence: 99%
“…This target seems to be involved in both DM1 and DM2 pathogeneses because both DM1 and DM2 are characterized by insulin resistance and predisposition to type 2 diabetes (T2D) [ 3 , 4 , 5 , 6 ]. It was shown that an anti-diabetic drug, metformin, corrects abnormal IR splicing in DM1 mesodermal precursor cells (MPCs) and in DM1 myoblasts ([ 78 ] and reviewed in [ 79 ]). Interestingly, in addition to IR, metformin also improves splicing of other genes, including TNNT2 and Clcn1 [ 78 ].…”
Section: Therapeutic Targets In Dm1 and Dm2mentioning
confidence: 99%
“…However, there is still a long way to go from animal experiments to human experiments to final clinical applications. Also, some studies reveal the efficacy of metformin delaying and/or limiting DM1, not only in diabetes, but also in additional characteristics of its pathobiology[ 26 ]. Besides, in our opinion, regular follow-up to assess lung function, oxygen saturation, ECG, and cardiac function is also critical.…”
Section: Discussionmentioning
confidence: 99%
“… Therapeutic approaches for DM1 discussed in the reviews in the Special Issues of the journal. They include the CRISPR/Cas approach [ 5 , 6 ], as well as the application of small molecules, restoring MBNL1 and CUGBP1 activities or correcting splicing via other RNA-binding proteins [ 7 , 8 , 9 , 10 ]. Although indirectly, several review papers referred to the use of AONs as a potential therapy for DM1 [ 5 , 7 , 8 , 10 , 11 , 12 ].…”
Section: Figurementioning
confidence: 99%
“…MicroRNAs altered in DM1 could also be used as biomarkers. The review by Dr. Munain’s group describes the recent data related to the potential role of small-molecule metformin for the treatment of DM1 [ 8 ]. Some studies showed that metformin improves the splicing of insulin receptors, misregulated in DM1.…”
mentioning
confidence: 99%
See 1 more Smart Citation